Bolivia's lithium frontier: Can public private partnerships deliver a minerals boom for sustainable development?. (20th March 2018) - Hancock, L.; Ralph, N.; Ali, S.H.
Abstract: Lithium is central at least in the short term, for transitions to renewable energy. Substantial deposits reside in South America's 'lithium triangle' in Bolivia, Argentina and Chile. Bolivia has promoted lithium industrialization through vertically integrated mineral development under resource nationalism and public-private partnerships with foreign corporations. Central to the Bolivian vision is a desire to harness the most environmentally appropriate technologies for national development and to move away from exploitative extractive models so prevalent in developing countries. Bolivia has been at the forefront of Global South climate change arguments about carbon debt and resource rights for just and fair sustainable development. We discuss the debate on cleaner production for lithium, challenges of Bolivia's lithium industrialization under Indigenous President Morales, and investigate how the desire for cleaner technologies has cultivated unusual governance arrangements via public private partnerships (PPPs) between state enterprises and foreign-owned private corporations. We consider this model for developing remote mineral reserves for advanced cleaner production technologies that are necessary for the transition from a fossil fuel to a low carbon global economy, alongside addressing sustainable development goals. Lithium is vital for energy storage, renewable energy and the electric vehicle industry. To meet rising lithium demand with minimal environmental and social impacts, novel approaches are needed to international resource extraction partnerships that transcend ideological biases; with their efficacy evaluated. Our research aims to pave the way to such an evaluative framework, using Bolivia's lithium as a central case. Key research issues for developing the framework and initial criteria of evaluation are proposed, focused on how public private partnerships interface with the United Nations Sustainable Development Goals (SDGs). Highlights: Lithium is key to transitions to clean energy technologies and offers development. Bolivian resource nationalism has led to a hybrid mineral development path. Public-private partnerships (PPPs) in mineral development need investor confidence. Evaluative frameworks for PPPs, and their development impacts, are thus needed. For sustainability, PPPs can link with the global Sustainable Development Goals (UN SDGs).